Cretaceous pollen cone with three‐dimensional preservation sheds light on the morphological evolution of cycads in deep time. Issue 4 (21st March 2023) - Elgorriaga, Andres; Atkinson, Brian A.
Summary: The Cycadales are an ancient and charismatic group of seed plants. However, their morphological evolution in deep time is poorly understood. While molecular divergence time analyses estimate a Cretaceous origin for most major living cycad clades, much of the extant diversity is inferred to be a result of Neogene diversifications. This leads to long branches throughout the cycadalean phylogeny that, with few exceptions, have yet to be rectified by unequivocal fossil cycads. We report a permineralized pollen cone from the Campanian Holz Shale located in Silverado Canyon, CA, USA ( c. 80 million yr ago). This fossil was studied via serial sectioning, SEM, 3D reconstruction and phylogenetic analyses. Microsporophyll and pollen morphology indicate this cone is assignable to Skyttegaardia, a recently described genus based on disarticulated lignitized microsporophylls from the Early Cretaceous of Denmark. Data from this new species, including a simple cone architecture, anatomical details and vasculature organization, indicate cycadalean affinities for Skyttegaardia . Phylogenetic analyses support this assignment and recover Skyttegaardia as crown‐group Cycadales, nested within Zamiaceae. Our findings support a Cretaceous diversification for crown‐group Zamiaceae, which included the evolution of morphological divergent extinct taxa with unique traits that have yet to be widely identified in the fossil record.